2007
DOI: 10.1111/j.1469-7580.2007.00764.x
|View full text |Cite
|
Sign up to set email alerts
|

Topographical and laminar distribution of cortical input to the monkey entorhinal cortex

Abstract: Hippocampal formation plays a prominent role in episodic memory formation and consolidation. It is likely that episodic memory representations are constructed from cortical information that is mostly funnelled through the entorhinal cortex to the hippocampus. The entorhinal cortex returns processed information to the neocortex. Retrograde tracing studies have shown that neocortical afferents to the entorhinal cortex originate almost exclusively in polymodal association cortical areas. However, the use of retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 26 publications
1
66
0
1
Order By: Relevance
“…In the present experiment, subjects were not submitted to any systematic memory task before sleep. Our results demonstrate that even under these conditions, slow oscillation is associated with consistent responses in the parahippocampal gyrus, a major relay area between the hippocampus and neocortex (22).…”
Section: Comparison With Earlier Positron Emission Tomography and Fmrmentioning
confidence: 84%
“…In the present experiment, subjects were not submitted to any systematic memory task before sleep. Our results demonstrate that even under these conditions, slow oscillation is associated with consistent responses in the parahippocampal gyrus, a major relay area between the hippocampus and neocortex (22).…”
Section: Comparison With Earlier Positron Emission Tomography and Fmrmentioning
confidence: 84%
“…However, studies in nonhuman primates suggest that the strongest PFC projections to the ERC and PRC arise in the orbitofrontal cortex (11)(12)(13). In contrast, structural connectivity between DLPFC/VLPFC and the MTL is light (10)(11)(12)(13). Therefore, the question whether prefrontal areas that show encoding-related activity patterns are connected with the ERC and PRC is particularly relevant in humans.…”
mentioning
confidence: 80%
“…Activity patterns that reflect successful encoding in functional MRI (fMRI) studies are most frequently observed in the ventrolateral and dorsolateral PFC (VLPFC and DLPFC, respectively) (6, 7). However, studies in nonhuman primates suggest that the strongest PFC projections to the ERC and PRC arise in the orbitofrontal cortex (11)(12)(13). In contrast, structural connectivity between DLPFC/VLPFC and the MTL is light (10)(11)(12)(13).…”
mentioning
confidence: 94%
“…Indeed, output connectivity of the primate hippocampus with subcortical areas -including nucleus accumbens 173 -follows a graded topography similar to that in rodents 174 (but note longitudinally restricted vs. distributed hippocampal-amygdala projections in primates and rodents, respectively 107,175 ). Input connectivity from entorhinal cortex to DG also follow a graded mapping that is analogous to that in rats [34][35] , with an anteromedial-posterolateral EC axis corresponding to an anterior-posterior DG termination [176][177][178] . For example, the pattern of connectivity between cingulate cortex and hippocampus in primates is similar to that in rats, in the sense that anterior hippocampus is more strongly connected with anterior regions and medial frontal cortex, and connections with posterior cingulate (including retrosplenial cortex) are stronger with posterior hippocampus [179][180] .…”
Section: Box 1 Is the Rodent Ventral-dorsal Axis Homologous To The Pmentioning
confidence: 99%